2016
DOI: 10.1249/mss.0000000000000967
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Training for Older Patients with Controlled Isolated Systolic Hypertension

Abstract: Slow breathing training, especially with an inspiratory load, is very effective in reducing resting systolic and pulse pressures and could be a valuable adjunct in the management of ISH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
1
27
0
4
Order By: Relevance
“…Further studies might, therefore, determine whether SLB can replace conventional pharmaceutical treatment and whether it is necessary for patients to train every day. The fact that the training effect persists for several weeks (Sangthong et al, and present results) suggests that once BP is reduced, it may be sufficient to train intermittently.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Further studies might, therefore, determine whether SLB can replace conventional pharmaceutical treatment and whether it is necessary for patients to train every day. The fact that the training effect persists for several weeks (Sangthong et al, and present results) suggests that once BP is reduced, it may be sufficient to train intermittently.…”
Section: Discussionsupporting
confidence: 54%
“…Guidelines for the management of hypertension focus very much on pharmacological treatments, lifestyle, and exercise training (James et al, ), and although these treatments can be effective, many patients remain poorly controlled (Chobanian, ; Mancia et al, ). Some other form of nonpharmacological treatment may be of benefit to these patients, and we have previously demonstrated that SLB is effective in reducing resting sBP (Sangthong et al, ; Ublosakka‐Jones et al, a). Although it is important to reduce resting BP, it would be valuable if the treatment also decreased the exaggerated increase in BP seen during exercise in ISH (Ubolsakka‐Jones et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations